Evaluación sensorial del cacao (theobroma ccaca L.)nacional fino o d aroma procedente de diferentes zonas del país. - Solórzano Chávez, Eddyn Gabriel (2011)
The research was conducted in the EET-Pichilingue INIAP. During the period December 2009 to May 2011. The research was aimed at identifying sensory profiles of cocoa liquor, for which samples were taken Nacional cacao beans "Flavor Arriba" from different regions of Ecuador in which 11 associations involved cocoa producer, located in seven provinces: Esmeraldas, Manabí, Guayas, Los Ríos, Bolivar, Sucumbíos and Orellana. The pattern of harvest was crucial to the collection of samples of fermented cocoa beans and dry, which took three times for each association, providing a total of 33 samples for the study, each sample was used 1 kg At that applied sensory analysis, having the need to prepare liquor or cocoa mass, the same is assessed the following variables: cocoa flavor, acidity, bitterness, astringency, sweet or sweet, floral, fruity, nutty. With the data matrix was created for statistical analysis using nonparametric tests (Kruskal & Wallis 5%) for comparison of flavors between samples and the group of individuals was related to him or predominant flavor profiles for each area by principal component analysis PCA. The results indicate that all samples have different profiles feelings and only cocoa flavor statistical differences were manifest, the intensity of this flavor associations allowed to identify you and Miss Ecuador APROCA are most important with respect to this attribute. Besides the Miss Ecuador cocoa flavor enhancer manifest expressions floral and fruity particularity of fine or flavor cocoa. Cocoa associates other as Eloy Alfaro, Buena Suerte, Fortaleza del Valle, San Carlos, showed potential with respect to the fruity flavor with hints of sweetness palatable, cocoa from other areas shows the attributes of cocoa fine but need to improve processes post-harvest.